An Introduction to Frank Zappa's 'Chord Bible'. (9th December 2016) - CLEMENT, BRETT
ABSTRACT: This article offers an introduction to a little‐known compositional system devised by Frank Zappa for his orchestral music: the Chord Bible. Through a close study of the orchestral works featuring Chord Bible harmony, I will attempt a partial recreation of its contents, focusing on seven‐ and eight‐note chords. This will reveal a hybrid system with important pitch and pitch‐class components. Regarding pitch, each chord manifests a precise intervallic spacing (or 'density', to use Zappa's term). Conversely, chords are conceived in a scalar harmonic universe derived from diatonic, minor Lydian and octatonic pitch‐class collections. These aspects will be described as a merging of features derived from the music of Edgard Varèse and from the scalar procedures characteristic of Zappa's popular output. I will demonstrate how different chord types within the Chord Bible are generated from a combination of scalar and intervallic transformations. The study concludes with an overview of the musical employment of Chord Bible harmony in three pieces. This analysis will reveal a progressive sophistication in technique that is directly related to the increased importance of the Chord Bible in Zappa's compositional process.